Kesalahan Siswa Dalam Menyelesaikan Soal Pada Materi Trigonometri Tahun Pelajaran 2019/2020 - Lalu Abdul Yasir; Sripatmi Sripatmi; Wahidaturrahmi; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to determine the percentage of each type of student error based on student achievement and the relationship between types of errors in solving trigonometric problems with overall errors. This research is a descriptive correlational research. The sample used in this study was 15% of all students in class XI MAN 1 Central Lombok in the 2019/2020 academic year including 8 low achieving students, 29 medium achieving students, and 5 high achieving students. The data in this study came from student test results. The test results data were analyzed to find out how big the percentage of errors made by students and how big the level of error relationship was based on the object of mathematical study which included factual errors, conceptual errors, operating errors and principle errors with overall errors. The results showed that the students of class XI MAN 1 Central Lombok had a percentage of errors based on student achievement, respectively, from high, medium and low achievers. Fact errors with percentages of 40%, 63% and 50%, respectively, are in the moderate category. Concept errors with percentages of 35%, 49% and 66%, respectively, are in the low category. Operational errors with percentages of 33%, 60% and 67%, respectively, are in the moderate category. Errors in principle with a percentage of 42%, 68% and 72%, respectively, are in the moderate category. The relationship between each error and the overall error is a factual error of 0.52 is moderate, a conceptual error of 0.85 is very strong, an operating error of 0.88 is very strong, and a principle error of 0.95 is very strong.